2021
DOI: 10.1002/srin.202100677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lance Design on Jet Characteristics in 250 t Converter

Abstract: The supersonic jet characteristics of the oxygen lance nozzle play an important role in converter melting. However, limited studies have investigated the different nozzle arrangements to improve the jet characteristics. This study uses FLUENT to establish a compressible nonisothermal computational fluid model with a 250 t converter as the object, and the model first validates and then discusses the effects of the center hole and postcombustion (PC) oxygen lance secondary hole on the aggregation behavior and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The outlet is connected with the atmosphere, and the outlet pressure is 0.1 MPa. [24,36] The mass flow rate and ambient temperature parameters of the 17 cases (case A1 to case D4) simulated are shown in Table 1. It is pointed out here that the main oxygen jet flow rate of the EAF varied in different smelting stages.…”
Section: Numerical Model and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outlet is connected with the atmosphere, and the outlet pressure is 0.1 MPa. [24,36] The mass flow rate and ambient temperature parameters of the 17 cases (case A1 to case D4) simulated are shown in Table 1. It is pointed out here that the main oxygen jet flow rate of the EAF varied in different smelting stages.…”
Section: Numerical Model and Boundary Conditionsmentioning
confidence: 99%
“…[19] Many scholars have conducted research on different types of oxygen jets through experiment and numerical simulation. [20][21][22][23] Liu et al [24] applied numerical simulation methods to study effects of the center hole and postcombustion oxygen lance secondary hole on the aggregation behavior and impact area of the oxygen jet based on the conventional five-hole oxygen lance. The results indicated that hole-secondary hole with center hole can significantly improve conventional oxygen jets.…”
mentioning
confidence: 99%
“…For example, such lances include the central subsonic oxygen lance, 14 double-parameter oxygen lance, 15,16 single-flow post-combustion oxygen lance 17 and post-combustion oxygen lance. 18 In addition, a swirl-type oxygen lance has been developed, as shown in Figure 1. Higuchi and Tago 19 used physical experiments to study the jet behaviour and splashing of swirl-type oxygen lance, and it was found that a swirl angle of 11.4° was most effective for reducing the splashing rate.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The shape and motion of this impact cavity depend on the parameters of the top nozzle, which directly influence the gas-liquid reaction interface, splashing behavior, and stirring ability of the molten pool. [5][6][7] Therefore, understanding the motion characteristics of the supersonic jet and its interaction with the molten pool is crucial for promoting the mixing and chemical reaction rate of molten metal, which promotes the homogenization of the molten metal temperature and composition and prolongs the service life of the oxygen lance.…”
Section: Introductionmentioning
confidence: 99%